Penerapan Metode MOORA dalam Penentuan Program MBKM Terbaik bagi Mahasiswa - Sagala, Anita Cayayuk Damayanti; Sagala, Teresia Tiurida (Edusia: Jurnal Ilmiah Pendidikan Asia, 2023)
This research describes the MOORA method in determining the best MBKM program for fifth-semester students at the Telkom Institute of Technology Purwokerto. The MOORA method has five stages. Data was obtained through distributing questionnaires filled in by fifth-semester students. In this research, respondents were obtained from Telkom Purwokerto Institute of Technology students to research the best MBKM program for fifth-semester students. This method does not require a mathematician to calculate using the MOORA method. The MOORA method is a multiobjective system method that optimizes several conflicting attributes simultaneously. Results of decision support research using the MOORA method to rank the best MBKM (Teaching Campus) programs for fifth-semester students. Based on student respondents' filling out questionnaires, the MBKM program that is most suitable and needed for students is Internship, followed by Bangkit by Google, Traveloka, and Goto, then Teaching Campus, and finally Independent Study.